Sosialisasi pentingnya menabung untuk anak usia dini di tk darul falah 10 samarinda - Reni Ardiana; Andi Aslindah; Rinawati Hartanti (Institute of Computer Science (IOCS), 2024)
The implementation of socialization regarding the importance of saving in early childhood at Darul Falah 10 Samarinda Kindergarten has been successfully carried out with a structured and systematic approach. The preparation process involves intensive coordination with the school, the use of materials appropriate for their age, and special training for facilitators. During the implementation of the activity, children were involved in interesting story interactions, the use of educational videos, as well as hands-on practice of saving using piggy banks and making bank visits. The evaluation of this activity showed the level of active participation of children and positive responses from teachers, with 90% of respondents considering this activity to provide significant benefits. It is hoped that this approach can contribute to helping children understand and apply sustainable saving habits, fully supported by the active role of schools and family support in forming a positive attitude towards financial management from an early age